Work Motivation and Principal Support Effects on Teachers' Readiness for Promotion in Indonesian Public Elementary Schools: A Multiple Regression Analysis - Weski Afrianto; Weni Yulastri; Alfroki Martha (Journal of Education Research, 2026)
Teacher readiness for professional promotion is a vital factor affecting instructional quality and the sustainability of human resources in elementary education. However, the organizational factors influencing this readiness are not well-studied in regional Indonesian contexts. This study aims to examine how work motivation and principal support impact teachers' readiness for promotion at public elementary schools in Tanah Cogok District. A quantitative method using multiple regression analysis was employed, with data collected from 85 teachers through validated questionnaires selected by proportional random sampling. The results show that both work motivation and principal support significantly and positively influence teachers' promotion readiness, both individually and together, explaining 50.4% of the variance in promotion readiness. Work motivation was identified as the stronger predictor (β = 0.452), highlighting the importance of intrinsic professional drive in preparing teachers for career advancement. These findings suggest that school principals and district education policymakers should develop targeted motivational programs and enhance principal leadership capacity to provide career-supporting strategies as a key part of elementary school human resource management.guru untuk promosi jabatan merupakan faktor penentu kualitas pembelajaran dan keberlanjutan sumber daya manusia di pendidikan dasar, namun faktor organisasional yang mendorong kesiapan tersebut masih belum banyak diteliti dalam konteks daerah di Indonesia. Penelitian ini mengkaji pengaruh motivasi kerja dan dukungan kepala sekolah terhadap kesiapan promosi guru di Sekolah Dasar se-Kecamatan Tanah Cogok. Pendekatan kuantitatif dengan analisis regresi berganda digunakan, dengan data dikumpulkan melalui kuesioner tervalidasi yang diberikan kepada 85 guru yang dipilih secara proportional random sampling. Hasil penelitian menunjukkan bahwa motivasi kerja dan dukungan kepala sekolah berpengaruh positif dan signifikan terhadap kesiapan promosi guru, baik secara parsial maupun simultan. Motivasi kerja muncul sebagai prediktor yang lebih dominan. Temuan ini menegaskan pentingnya pengembangan motivasi intrinsik guru dan penguatan dukungan institusional dalam meningkatkan kesiapan pengembangan karier profesional.   Abstract   Teacher readiness for professional promotion is a critical determinant of instructional quality and human resource sustainability in elementary education, yet the organizational factors that drive such readiness remain insufficiently studied in regional Indonesian contexts. This study investigates the effects of work motivation and principal support on teachers' readiness for promotion at elementary schools in Tanah Cogok District. A quantitative approach using multiple regression analysis was employed, with data collected through validated questionnaires administered to 85 teachers selected via proportional random sampling. Results indicate that both work motivation and principal support have significant positive effects on teacher promotion readiness, individually and simultaneously. Work motivation emerged as the stronger predictor. These findings suggest that school organizations must cultivate intrinsic teacher motivation and strengthen institutional support mechanisms to enhance readiness for professional advancement, with implications for principal leadership development and human resource management policy.